Effects Of Mg, Si And Cu On Ageing Response Of Dilute 6XXXX Series Aluminium Alloys - Jaafar, Che Nor Aiza (2011)
The effects of magnesium (Mg), silicon (Si) and copper (Cu) on ageing response of heat treatable dilute 6xxx series aluminium alloys have been investigated. The alloys contained between 0.22 to 0.79 wt% Si and 0.20 to 0.51 wt% Mg. In this study, some alloys contained 0.1 wt% Cu and others contained 0.001 to 0.002 wt% Cu which were considered as Cu-free alloys. In order to study the effect of composition on the ageing response, the alloys samples were solution treated at 530  5 oC for 5 minutes and then water quenched into ice water at 0 oC before naturally aged at room temperature and artificially aged at elevated temperature.